ناكۆكی نێوان هاوسه‌ران و لێكه‌وته‌ كۆمه‌ڵایه‌تییه‌كانی - فر‌ج, پ. د. نجاة محمد; جافر, مروان مظهر (Sulaimani Journal for Humanities, 2023)
One of the negative factors that affects marriage is the existence of constant conflict between spouses, in the event of not being resolved or under control, various types of negative relationships between spouses may be followed. The door to dialogue and understanding is closed. Wise thinking and the ability to communicate healthily will be disabled, and the bad reaction of anger closes the door of dialogue and understanding. Although, the conflict between spouses is a natural and inevitable issue, even it is the mark of family life, but if spouses are unable to manage and organize it, it will lead the future of the family to a dangerous point till arriving the point of divorce. In which, spouses and children themselves are the victims of this conflict. This study, based on the Grounded Theory Method as one of the methods of Qualitative Research tries to realize the social consequences of spouse’s disputes in a real way, through both the tools of interview and observing a number of scientific results.
Keywords: (ناكۆكی ناكۆكی هاوسەری لێكەوته)